Perancangan Playbook Identifikasi Serangga Sebagai Bahan Penunjang Pembelajaran IPA di Bakal Sekolah Alam Kampung Wisata Isyo Hills Rhepang Muaif, Nimbokrang, Kabupaten Jayapura - Evie L. Warikar; Euniche R.P.F. Ramandey; Henderina J. Keiluhu (Bakti Hayati: Jurnal Pengabdian Indonesia, 2022)
The purpose of this activity is to design an insect identification playbook and introduce and directly practice insect identification through this playbook to teachers and elementary school students at Sekolah Alam "Isyo Hills" Kampung Rhepang Muaif, Nimbokrang, Jayapura Papua. The method used in this design begins with the phase of making the playbook material concept, making the design and choosing characters to layout, and the finalization stage for the final result. This design produced a playbook in the form of a books by displaying the discussion of the material insect introduction with coloring activities for insects namely Odonata (dragonflies and damselflies), Lepidoptera (butterflies and moths) and Coleoptera (beetles). The next activity is training which is carried out on July 2021, involving 11 students, representatives of elementary school grades 1 to 5 and junior high school from Sekolah Alam â€˜â€™Isyo Hillsâ€. The training provided includes the presentation regarding the introduction of insects through the design of playbook. Furthermore students directly practice the coloring activities for several species examples of insects in the playbook. The training which was conducted for the teacher and students at Sekolah Alam â€œIsyo Hillsâ€ Kampung Rephang Muaif has been going well. The enthusiasm of the participants in participating in this training was very high. This indicates that the training participants have responded positively to the activities that have been carried out.Â Keywords:Â training; design of playbook; insect; Rephang Muaif.Â